Coordinated operation strategies for natural gas and power systems in presence of gas-related flexibilities - Ameli,H; Qadrdan,M; Strbac,G (IET Energy Systems Integration, 2019)
A detailed investigation of interaction between natural gas and power systems is necessary, due to the increasinginterdependency of these vectors, especially in the context of renewable generations integration growth into the grid. In this paper,an outer approximation with equality relaxation decomposition method is proposed to solve a mixed-integer non-linear problemrepresenting the operation of coupled natural gas and power systems. The proposed coupled modeling of natural gas and powersystems is compared to a decoupled operational modeling. It is demonstrated that operating gas and electricity as a coupledsystem resulted in about 7% operational cost savings. In addition, the value of gas-related flexibility options, including flexiblegas compressors, flexible gas generation plants, and gas interconnections, to the operation of natural gas and power systems isquantified for a 2030 GB energy system. It is shown that if the natural gas and power systems are flexible enough, operation of thesystems in the decoupled approach is almost the same as the coupled model and therefore there is no need to reform the currentenergy market framework to make the systems fully coupled.